Cover Feature: Potent and Selective Cytotoxic and Anti‐inflammatory Gold(III) Compounds Containing Cyclometalated Phosphine Sulfide Ligands (Chem. Eur. J. 62/2019). Issue 62 (2nd October 2019) - Reddy, T. Srinivasa; Pooja, Deep; Privér, Steven H.; Luwor, Rodney B.; Mirzadeh, Nedaossadat; Ramesan, Shwathy; Ramakrishna, Sistla; Karri, Shailaja; Kuncha, Madhusudana; Bhargava, Suresh K.
Abstract : Newly designed gold(III) compounds containing cycloaurated phosphine sulfide ligands with dual properties, namely anti‐cancer and anti‐inflammatory activity, offer a safe and effective treatment for cancer. A common drawback of gold(III) complexes is their instability under physiological conditions, which has been overcome by shedding light on the desirable ligand features that stabilize gold compounds, making them suitable for biological investigations. More information can be found in the Full Paper by R. B. Luwor, N. Mirzadeh, S. K. Bhargava et al. on page 14089 .